Transfer Pricing, Information Asymmetry, Thin Capitalization, and Intangible Assets: Their Influence on the Utilization of Tax Havens – Evidence from Mining Companies (2020–2024) - Pamelia Agustine; Etty Herijawati (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Income tax remains the main contributor to Indonesia’s tax revenue; therefore, the government aims to boost its income through the taxation sector, both corporate and individual income taxes. The study is designed to assess the various aspects that shape the utilization of tax havens by firms, particularly within the mining field. Multinational corporations often utilize tax havens as a means of reallocating profits to Tax-friendly jurisdictions, thereby Cutting down their aggregate tax burden. This study applies multiple linear regression analysis using secondary data derived from corporate financial reports. The F-test outcomes indicate that, collectively, Tax haven usage is significantly affected by the four independent variables, with an F-value of 4.446 > F-table value of 2.43 and a significance level of 0.006 < 0.05. The t-test results indicate that transfer pricing (t = 2.172; sig. = 0.032), thin capitalization (t = 2.716; sig. = 0.007), and intangible assets (t = 2.646; sig. = 0.009) significantly influence the utilization of tax havens.